Environmental Factors Impacting Heavy Metal Contamination of Mango Fruits and Health Implications on Consumers: A Biochemical Analysis - Onah, Donatus; Nkpa, Oluchukwu; Yarkwan, Baturh (British Journal of Healthcare and Medical Research, 2026)
Mango (Mangifera indica L) is a cherished fruit in many continents. It has a high trade value and economic importance due to its production and sales. However, anthropogenic activities have often impacted the quality, creating contaminated fruits for human consumption. This review of recent literature highlights the staple nature of the fruit and its contributions to the caloric value of its consumers. However, different environmental practices, ranging from natural causes to anthropogenic activities such as industrial production, agrochemical uses and discharges, vehicular traffic, create sources of pollution to the mango fruit. Fruit contamination is rampant in Africa and Asia, predisposing consumers to chronic toxicity. The public health impact may be through pathologies initiated by heavy metal poisoning owing to accumulation in different body tissues such as bones, brain, liver, and kidneys. Molecular basis for heavy metals update and toxicities were discussed. Proactive and corrective strategies were made to manage agricultural soils and safeguard the public from consuming heavy metals-contaminated mangoes.